2022
DOI: 10.1101/2022.10.19.512959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mating activates neuroendocrine pathways signaling hunger inDrosophilafemales

Abstract: Mated females reallocate resources to offspring production, causing changes in nutritional requirements and challenges to energy homeostasis. Although observed in most species, the neural and endocrine mechanisms that regulate the nutritional needs of mated females are not well understood. Here, we investigate the neural circuitry that regulates sugar appetite in matedDrosophila melanogasterfemales. During copulation, a male-derived sex peptide is transferred to females, silencing the mating status circuit to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…We characterized the pathway from the second-order BiT projection neuron that oppositely regulates sugar and water consumption. We found that BiT has 93 synaptic partners, including IPCs which are known to modulate food intake (Nässel & Zandawala, 2020), FLAa3/Lgr3 which have been implicated in regulating ingestion 22 (Laturney et al, 2022, Meissner et al, 2016, Nässel et al, 2013, Yeom et al, 2021, and neurons labeled by the CCHa2R-RA-Gal4 (Deng et al, 2019) which we found regulate water ingestion. BiT downstream neurons innervate several neuropils including the SEZ, SMP, SLP, fan shaped body, and lobula.…”
Section: The Isns Influence Activity Of Several Brain Regions Involve...mentioning
confidence: 63%
“…We characterized the pathway from the second-order BiT projection neuron that oppositely regulates sugar and water consumption. We found that BiT has 93 synaptic partners, including IPCs which are known to modulate food intake (Nässel & Zandawala, 2020), FLAa3/Lgr3 which have been implicated in regulating ingestion 22 (Laturney et al, 2022, Meissner et al, 2016, Nässel et al, 2013, Yeom et al, 2021, and neurons labeled by the CCHa2R-RA-Gal4 (Deng et al, 2019) which we found regulate water ingestion. BiT downstream neurons innervate several neuropils including the SEZ, SMP, SLP, fan shaped body, and lobula.…”
Section: The Isns Influence Activity Of Several Brain Regions Involve...mentioning
confidence: 63%
“…We characterized the pathway from the second-order BiT projection neuron that oppositely regulates sugar and water consumption. We found that BiT has 93 predicted synaptic partners, including IPCs which are known to modulate food intake ( Nässel and Zandawala, 2020 ), FLAa3/Lgr3 which have been implicated in regulating ingestion ( Laturney et al, 2022 ; Meissner et al, 2016 ; Nässel et al, 2013 ; Yeom et al, 2021 ), and neurons labeled by the CCHa2R-RA-Gal4 ( Deng et al, 2019 ) which we found to regulate water ingestion. BiT downstream neurons innervate several neuropils including the SEZ, SMP, SLP, FB, and lobula.…”
Section: Discussionmentioning
confidence: 80%
“…CDM and PPPM search approaches both find valid EM/LM matches for several tested neurons, supporting their effectiveness and the good coverage of the brain by the Gen1 MCFO collection. NeuronBridge has already seen frequent usage ( Bidaye et al, 2020 ; Morimoto et al, 2020 ; Nojima et al, 2021 ; Sareen et al, 2021 ; Zolin et al, 2021 ; Israel et al, 2022 ; Tanaka and Clark, 2022 ; Laturney et al, 2022 ). Together these tools allow for the rapid determination of likely split-GAL4 lines and other enhancer-based approaches to target most neurons initially found in the FlyEM Hemibrain and eventually in the full Drosophila CNS.…”
Section: Discussionmentioning
confidence: 99%